Fungal extracellular vesicle-mediated regulation: from virulence factor to clinical application - Liu, Jie; Hu, Xiaoping (Frontiers in Microbiology, 2023)
Invasive fungal disease (IFD) poses a significant threat to immunocompromised patients and remains a global challenge due to limited treatment options, high mortality and morbidity rates, and the emergence of drug-resistant strains. Despite advancements in antifungal agents and diagnostic techniques, the lack of effective vaccines, standardized diagnostic tools, and efficient antifungal drugs contributes to the ongoing impact of invasive fungal infections (IFI). Recent studies have highlighted the presence of extracellular vesicles (EVs) released by fungi carrying various components such as enzymes, lipids, nucleic acids, and virulence proteins, which play roles in both physiological and pathological processes. These fungal EVs have been shown to interact with the host immune system during the development of fungal infections whereas their functional role and potential application in patients are not yet fully understood. This review summarizes the current understanding of the biologically relevant findings regarding EV in host-pathogen interaction, and aim to describe our knowledge of the roles of EV as diagnostic tools and vaccine vehicles, offering promising prospects for the treatment of IFI patients.